The effect of peer tutoring and explicit instructional strategies on primary school pupils learning outcomes in mathematics (2013)
The study investigated the effect of explicit and peer tutoring instructional strategies (treatment), pupils ability and gender on learning outcomes in primary school Mathematics. Data analysis involved the use of analysis of covariance (ANCOVA). The sample consisted of 170 primary 5 pupils selected through simple random from eight schools. The findings revealed that there was significant main effect of treatment on achievement in Mathematics and attitude towards Mathematics. Pupil's ability and gender were found not to have significant main effect on achievement in Mathematics and attitude toward Mathematics. However there was a significant interaction effect of treatment and pupils’ ability on pupils’ attitude towards Mathematics. All the two and three ways interaction effects on achievement and attitude were found not to be significant. These findings and application indicate that the significant main effect of treatment on mathematics achievement and attitude respectively provide empirical basis to suggest that primary school practicing Mathematics teacher should constantly use peer-tutoring and explicit teaching instructional strategies in Mathematics classrooms. The use of these instructional strategies in improving Mathematics achievement and attitude toward the subject should also be encouraged irrespective of student pupil’s ability and gender. There is also a need for developers of curriculum materials (e.g. teacher trainee's, textbook associated trainer's guide) in Mathematics methodology to incorporate the significant findings of the present study. The textual material should contain detail of hour peer-tutoring and explicit -teaching instructional strategies could be made an integral part of Mathematics teaching at the primary school level.